2022
DOI: 10.1002/jbm.a.37361
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional‐printed polycaprolactone/polypyrrole conducting scaffolds for differentiation of human olfactory ecto‐mesenchymal stem cells into Schwann cell‐like phenotypes and promotion of neurite outgrowth

Abstract: Implantation of a suitable nerve guide conduit (NGC) seeded with sufficient Schwann cells (SCs) is required to improve peripheral nerve regeneration efficiently. Given the limitations of isolating and culturing SCs, using various sources of stem cells, including mesenchymal stem cells (MSCs) obtained from nasal olfactory mucosa, can be desirable. Olfactory ecto-MSCs (OE-MSCs) are a new population of neural crestderived stem cells that can proliferate and differentiate into SCs and can be considered a promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…[ 33 , 49 ]. In recent years, various approaches have been developed to promote induction of MSCs into Schwann-like cells, particularly the use of certain small molecules or growth factors [ 48 , 50 ] and engineered substrates or scaffolds such as graphene oxide substrate [ 51 ], 3D-printed polycaprolactone/polypyrrole (PCL/PPy) conductive scaffold [ 52 ], 3D-printed bionic polycaprolactone (PCL) polymer scaffold [ 53 ], and aligned nanofibers [ 54 ]. Consistent with our recent studies [ 37 ], we, herein, have also demonstrated that GMSCs could directly and rapidly convert into Schwann-like cells when they were encapsulated in methacrylated 3D-collagen hydrogel and cultured under the regular MSC culture medium without the additional introduction of special nutritional and growth factor supplements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 , 49 ]. In recent years, various approaches have been developed to promote induction of MSCs into Schwann-like cells, particularly the use of certain small molecules or growth factors [ 48 , 50 ] and engineered substrates or scaffolds such as graphene oxide substrate [ 51 ], 3D-printed polycaprolactone/polypyrrole (PCL/PPy) conductive scaffold [ 52 ], 3D-printed bionic polycaprolactone (PCL) polymer scaffold [ 53 ], and aligned nanofibers [ 54 ]. Consistent with our recent studies [ 37 ], we, herein, have also demonstrated that GMSCs could directly and rapidly convert into Schwann-like cells when they were encapsulated in methacrylated 3D-collagen hydrogel and cultured under the regular MSC culture medium without the additional introduction of special nutritional and growth factor supplements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PC12 cells co-cultured with stem cells exhibit extended neurite outgrowth, suggesting their potential for neuronal regeneration. 130 Compared to regular PPy homopolymers, the amine-functionalized polypyrrole (APPy) exhibits an average hydrophilic surface and electrical activity. In addition, APPy showed superior attachment to Schwann cells and human dermal fibroblasts under serum-containing and serum-free conditions.…”
Section: Peripheral Nerve Tissue Engineeringmentioning
confidence: 99%
“…Similar effects were reported from 3D-bioprinted cultures with aligned fibrin fibers in print strands [ 325 , 342 ]. Furthermore, polymer fibers manufactured from conductive materials and enabling electrostimulation of cells enhanced cell proliferation, migration, and differentiation [ 355 , 371 , 372 , 373 , 374 ]. Besides the composition and micropatterning, the stiffness is another important parameter of 3D culture materials.…”
Section: Trends In Schwann Cell 3d Culturementioning
confidence: 99%